Perinatal Outcome Associated with Meconium Stained Amniotic Fluid In Pregnancy (Journal of Paediatric Surgeons of Bangladesh, 2015)
Objectives: To evaluate perinatal outcome associated with meconium stained amniotic fluid in pregnant women.Methods: It was a prospective cross sectional study, conducted in the Department of Obstetrics and Gynecology in Bangabandhu Sheikh Mujib Medical University, Dhaka, from January 2013 to December 2013. Total 50 pregnant women admitted in the labour ward for delivery with meconium stained amniotic fluid were the study population. Singleton pregnancy of more than 34 weeks duration was included and pregnancy with APH, breech presentation, congenital malformation of fetus, IUD were excluded from the study. Out of 50 patients two did not provide all the information needed to analyze the data and hence were excluded. Outcome Variables were gestational age, antenatal checkup, medical diseases of mother (HTN, Diabetes mellitus, Heart disease), obstetric complication (oligohydramnios, prolonged labour), mode of delivery, neonatal details (weight of the baby in kg, APGAR scoring at 1 min & 5 min), neonatal resuscitation, admission in neonatal ICU(NICU), neonatal complications (RDS, MAS, Neonatal death).Results: Over half (52.1%) of the neonates needed resuscitation and 54.2% admitted in ICU. About 90% of the neonates had normal birth weight and only 10.4% were of low birth weight. 14.6% of the neonates developed meconium aspiration syndrome and 10.4% respiratory distress syndrome. Neonatal jaundice and neonatal sepsis were observed in 4.2% neonates each. Four neonates (8.3%) died early in the neonatal life, while 1 (2.1 %) was still-born. Low APGAR score (